Synthesis and characterization of tri- and tetra-metallic complexes of N’1,N’4-bis((E)-3,4-dihydroxybenzylidene)-succinohydrazide - El-Asmy, Ahmed Abd-Elhamied; Jeragh, Bakir; Ali, Mayada Samir (European Journal of Chemistry, 2016)
Single crystal of N’1,N’4-bis((E)-3,4-dihydroxybenzylidene)succinohydrazide (SHBH) was grown by slow evaporation method. Its, Co(II), Ni(II), Cu(II), Zn(II), Co(II)/Zn(II), Ni(II)/Zn(II) and Cu(II)/Zn(II) complexes have been prepared and characterized by elemental analysis, UV-Vis, IR, NMR, MS spectra, thermal and magnetic measurements. The data confirm the formation of tri- and tetra-metallic complexes (homo- and hetero-nuclear). The ligand behaves as a tetranegative hexadentate in the Co(II)/Zn(II) complex; hexanegative hexadentate in the Co(II) complex and hexanegative octadentate in the tetrametallic complexes. A square-planar for [Co3(SHBH-6H)(H2O)6], [Cu4(SHBH-H)(H2O)4(OAc)2]⋅3H2O, [Ni3Zn(SHBH-6H)(H2O)6Cl2]⋅H2O and [Cu3Zn(SHBH-6H)(H2O)6Cl2] and tetrahedral for [Ni4(SHBH-H)(H2O)4(OAc)2]⋅6H2O, [Zn3(SHBH-4H)-(H2O)4Cl2]⋅2H2O and [Co2Zn(SHBH-6H) (H2O)6Cl2]⋅2H2O were suggested based on the magnetic and spectral data. The TGA data confirm hydrated and coordinated water as well as the final product. The mass spectra depict their molecular ion peaks and the isotopic species of each complex. It is found that the homometallic complexes are highly stable than the heterometallic complexes. The calculated energies for [Co2Zn(SHBH-4H)(H2O)4Cl2].2H2O are higher than [Co3(SHBH-6H)-(H2O)6] indicating that the three Co stabilized the complex.